Best Management Practice guidelines (BMPs) for GIFT tilapia & Curriculum for the Promotion of Commercial Aquaculture in Nigeria - Salin, Krishna; Subasinghe, Rohana (WorldFish, 2022)
As part of the GIFT-related WorldFish projects operating in Nigeria, there is a need for developing (a) BMPs and related guidelines, and (b) training material to train stakeholders to implement BMPs in Nigeria. This manual includes best management practice guidelines for GIFT tilapia hatchery and grow out operations, including the curriculum for BMPs.